The Use of the Marine Microalga Tisochrysis lutea (T-iso) in Standard Toxicity Tests; Comparative Sensitivity With Other Test Species - Tato, Tania; Beiras, Ricardo (Frontiers in Marine Science, 2019)
The marine flagellate Isochrysis galbana, with a global distribution, is one of the most common microalgae used as natural food in aquaculture. In recent years I. galbana has been also increasingly used in toxicity testing, although it is not included in current international protocols such as ISO that relies on Phaeodactylum tricornutum and Skeletonema costatum as marine species, and Raphidocelis subcapitata as freshwater species. Sensitivity of I. galbana to selected model toxicants was compared with that of those recommended species using the 72h growth-rate inhibition response. Internationally accepted standard methods with fixed test conditions (light intensity, photoperiod, temperature, nutrients concentrations, initial cell density, time of exposure and endpoint) were followed to allow this comparison. Toxicity of model chemicals representative of the main environmental toxicants: a trace metal (zinc), a polyaromatic hydrocarbon (fluoranthene), an herbicide (benzalkonium chloride), an insecticide (chlorpyrifos), a surfactant (4-nonylphenol), and a microbiocide (triclosan) were evaluated to determine EC50 and EC10 values. In general, I. galbana showed higher sensitivity for most groups of toxicants, meeting the acceptability criteria in terms of control growth set in standard protocols. For example EC50 and EC10 of I. galbana for chlorpyrifos were 246 µg L-1 and 132 µg L-1, whereas for P. tricornutum these values were ca. 5-fold higher: 1117 and 746 µg L-1 respectively. Therefore, the use of I. galbana in marine toxicity testing as standard model representative of photosynthetic organisms is recommended.